Trust-based Selfish Node Detection Mechanism using Beta Distribution in Wireless Sensor Network - Kanchana Devi V; Ganesan R (LPPM ITB, 2019)
Wireless sensor networks (WSNs) are placed in open environments for the collection of data and are vulnerable to external and internal attacks. The cryptographic mechanisms implemented so far, such as authorization and authentication, are used to restrict external sensor node attacks but cannot prevent internal node attacks. In order to evade internal attacks trust mechanisms are used. In trust mechanisms, firstly, the sensor nodes are monitored using the popular Watchdog mechanism. However, traditional trust models do not pay much attention to selective forwarding and consecutive packet dropping. Sometimes, sensitive data are dropped by internal attackers. This problem is addressed in our proposed model by detecting selective forwarding and consecutive failure of sending packets using the Beta probability density function model.